PENGARUH PROFITABILITAS, STRUKTUR AKTIVA, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL (Studi Pada Perusahaan Perbankan yang Terdaftar di BEI periode 2015-2017) - Zila Nurdila Hafidzah; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT         This study aims to examine and analyze the effect of profitability, asset structure and firm size on the capital structure of a banking sector manufacturing company listed on the Indonesia Stock Exchange. The population is the 2015-2017 go public banking company of 43 companies, and the sample is 31 companies. Data collection through financial report data available on the IDX. Data analysis in this study uses the help of SPSS version 22 for windows. The sampling method with purposive sampling. The researcher used several tests including descriptive test, normality test, classic assumption test, multiple linear regression analysis, and testing the research hypothesis.The results of the analysis show that partially the asset structure does not significantly influence the capital structure because it is caused by the type of assets that can be guaranteed, and the fixed assets owned by the company are not so many multipurpose assets that are not so guaranteed while the profitability and size of the company significantly influence the capital structure. Together, it shows that profitability, asset structure and company size have a significant effect on capital structure.Keywords: Profitability, Asset Structure, Company Size and Capital Structure